Comparison of Magnesium and Zinc in Cationic π-Arene and Halobenzene Complexes - Friedrich, Alexander; Eyselein, Jonathan; Langer, Jens; Harder, Sjoerd (Organometallics, 2021)
The reaction of (tBuBDI)ZnEt with [Ph3C+][B(C6F5)4-] yielded the cation (tBuBDI)Zn+ (tBuBDI = CH[C(tBu)N-DIPP]2, DIPP = 2,6-diisopropylphenyl). The cation is sterically too shielded to interact with the ion B(C6F5)4- but forms complexes with arenes (benzene, toluene, m-xylene) or halobenzenes (PhX: X = F, Cl, Br, I). Crystal structures of these complexes are compared with those of the corresponding Mg complexes. Although Mg2+ and Zn2+ are of equal size, the Zn···arene and Zn···XPh contacts are generally 0.1-0.2 Å shorter than comparable contacts to (tBuBDI)Mg+. This originates from differences in bond character: bonding to Mg has a more electrostatic nature. A major difference between Mg and Zn is observed for PhF complexation. While the hard Mg2+ cation prefers Mg···FPh bonding, the softer Zn2+ shows a Zn···( π)PhF interaction. Heavier halobenzenes with softer halogens (Cl, Br, I) show Zn···XPh bonding. DFT calculations on (tBuBDI)Zn+···XPh (X = F, Cl, Br, I) show decreasing Zn···X-Ph angles from PhF to PhI on account of the increase in the halogen's σ-hole. Zn···XPh interactions result in C-X bond lengthening, but C-X bond activation is less pronounced than in corresponding Mg···XPh complexes. Weak (tBuBDI)Zn+···XPh bonding could not be detected in solution but is believed to play a role in the functionalization of organohalides by Zn reagents.
CRIS-Team Scopus Importer:2021-03-26